Monotone Iterative Solutions for Nonlinear Boundary Value Problems of Fractional Differential Equation - Chaozhu Hu; Bin Liu; Songfa Xie (Abstract and Applied Analysis)
By means of the method of quasi-lower and quasi-upper solutions and monotone iterative technique, we consider the nonlinear boundary value problems with Caputo fractional derivative and introduce two well-defined monotone sequences of quasi-lower and quasi-upper solutions which converge uniformly to the actual solution of the problem, and then the existence results of the solution for the problems are established. A numerical iterative scheme is introduced to obtain an accurate approximate solution and to give one example to demonstrate the accuracy and efficiency of the new approach.